2018
DOI: 10.1037/ccp0000277
|View full text |Cite
|
Sign up to set email alerts
|

In psychotherapy with severe patients discouraging news may be worse than no news: The impact of providing feedback to therapists on psychotherapy outcome, session attendance, and the alliance.

Abstract: Providing feedback to therapists without offering them tools to improve treatment may be ineffective and even be detrimental. This may be especially the case for patients who suffer more severe mental health issues and whose therapists receive mostly discouraging news as feedback. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Research on another feedback system, the OQ-45, points in the same direction. In Chile, Errázuriz & Zilcha-Mano (2018) included 547 patients and found that feedback concerning negative progress (compared to positive progress) had a negative impact on outcome, specifically for "severe patients" who had high baseline symptomatology and previous psychiatric hospitalizations. In a systematic review with 11 studies (nine on the OQ-45 and two on the PCOMS) a diminishing effect of feedback with more patient severity was found (Davidson, Perry, & Bell, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research on another feedback system, the OQ-45, points in the same direction. In Chile, Errázuriz & Zilcha-Mano (2018) included 547 patients and found that feedback concerning negative progress (compared to positive progress) had a negative impact on outcome, specifically for "severe patients" who had high baseline symptomatology and previous psychiatric hospitalizations. In a systematic review with 11 studies (nine on the OQ-45 and two on the PCOMS) a diminishing effect of feedback with more patient severity was found (Davidson, Perry, & Bell, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the efficacy of feedback to therapists on their patients' progress in treatment, based on patient-reported symptom severity, has shown promising findings (Lambert, 2013). Yet, feedback to therapists based on patients' reported alliance may not be effective (Errázuriz & Zilcha-Mano, 2018). A critical shortcoming of existing trials providing feedback to therapists on the alliance is their exclusive dependence on patient self-reports, which may reveal confrontational ruptures that the therapist is already aware of, but not withdrawal ruptures, about which the therapist needs the feedback to gain awareness.…”
Section: Open Questions and Directions For Future Researchmentioning
confidence: 99%
“…However, none of the six studies included in this analysis specifically compared the use OQ-45 alone to the use of both OQ-45 and CSTs. More recent dismantling studies have not found alliance feedback to augment ROM’s effect on treatment outcomes (Mikeal, Gillaspy, Scoles, & Murphy, 2016; Errázuriz & Zilcha-Mano, 2018) or the working alliance (Reese et al, 2013). This suggests that merely providing alliance feedback to therapists may not be sufficient to improve the alliance.…”
Section: Discussionmentioning
confidence: 95%
“…The heterogeneity in results between studies is substantial (Østergård et al, 2018). Some studies have reported null-findings (e.g., Davidsen et al, 2017; Hansson, Rundberg, Österling, Öjehagen, & Berglund, 2013; Rise, Eriksen, Grimstad, & Steinsbekk, 2016) and others, indications of adverse effects of ROM (de Jong, Segaar, Ingenhoven, van Busschbach, & Timman, 2018; Errázuriz & Zilcha-Mano, 2018; van Oenen et al, 2016). The mixed findings highlight the need for a more nuanced understanding of how the process works, a question which, to date, has received limited research attention (Wampold, 2015).…”
mentioning
confidence: 99%